Clinical crown length. Case report - Sánchez Moscoso, Mateo Steven (2023)
Introduction. Crown lengthening is one of the most frequently performed surgical procedures in periodontics, with a prevalence of 10%. Aim. Describe a periodontal technique to lengthen a clinical crown. Materials and methods. Through a clinical case, we will report the surgical approach to lengthen the clinical crown in the anterior sector. This surgical technique is based on restoring the biological space towards a more apical position before a prosthetic treatment to avoid its invasion that could result in bone resorption, gingival recession, inflammation or hypertrophy. Results: The technique allowed an improvement in periodontal health and the continuation of prosthetic treatment. conclusions. Through this treatment it is possible to rehabilitate dental organs to serve as supports and/or pillars for future dental prostheses.